Increasing Peroxide Number of Sumbawa Oil Through Ozonation Process Using Double Dielectric Barrier Discharge (DDBD) Plasma Reactor - Puryadi, Puryadi; Hilmi, Amirul; Ulfa, Andi Maria (Jurnal Pijar Mipa, 2024)
Oil is one of the most popular media for the ozonation process compared to other media such as water or saline methods or direct exposure to blood. Ozonated oil has an advantage over other ozone therapy methods because ozonated oil has an antiseptic activity that is several hundred times higher than ozonated saline. Sumbawa oil is one of the local wisdom products of the Sumbawa tribal community, which is generally used as medicine or massage therapy to heal injuries such as broken bones, tendonitis, bruises, back pain and treatment of various skin wounds. An ozonation process can be carried out to increase the ability of Sumbawa oil to regenerate skin and repair tissue. Ozonation uses a Double Dielectric Barrier Discharge (DDBD) plasma reactor. The DDBD Plasma Reactor is a reactor that can produce ozone gas with very high purity. Pure ozone gas is very well applied in the medical world. This research aims to increase the peroxide levels in Sumbawa oil by ozonation using a Double Dielectric Barrier Discharge (DDBD) Plasma reactor. The flow rates used were 0.1 L/minute, 0.4 L/minute and 0.7 L/minute for 1 hour, 3 hours and 5 hours. The results showed that the peroxide value increased with increasing oxygen flow rate and ozonation time. The highest peroxide value was obtained at a flow rate of 0.7 L/minute for 5 hours, namely 332.03 mg Eq/kg Sumbawa oil. Increased by 282.71 mg Eq/kg; the peroxide figure for Sumbawa oil without ozonation was 49.32 mg Eq/kg.